The Hyper Suprime-Cam SSP transient survey in COSMOS: Overview. (30th May 2019) - Yasuda, Naoki; Tanaka, Masaomi; Tominaga, Nozomu; Jiang, Ji-an; Moriya, Takashi J; Morokuma, Tomoki; Suzuki, Nao; Takahashi, Ichiro; Yamaguchi, Masaki S; Maeda, Keiichi; Sako, Masao; Ikeda, Shiro; et al.
Abstract: We present an overview of a deep transient survey of the COSMOS field with the Subaru Hyper Suprime-Cam (HSC). The survey was performed for the 1.77 deg 2 ultra-deep layer and 5.78 deg 2 deep layer in the Subaru Strategic Program over six- and four-month periods from 2016 to 2017, respectively. The ultra-deep layer reaches a median depth per epoch of 26.4, 26.3, 26.0, 25.6, and 24.6 mag in g, r, i, z, and y bands, respectively; the deep layer is ∼0.6 mag shallower. In total, 1824 supernova candidates were identified. Based on light-curve fitting and derived light-curve shape parameter, we classified 433 objects as Type Ia supernovae (SNe); among these candidates, 129 objects have spectroscopic or COSMOS2015 photometric redshifts and 58 objects are located at z > 1. Our unique data set doubles the number of Type Ia SNe at z > 1 and enables various time-domain analyses of Type II SNe, high-redshift superluminous SNe, variable stars, and active galactic nuclei.